Natural rubber/wood composite foam: Thermal insulation and acoustic isolation materials for construction - Neves de Alencar, Laura [UNESP]; Guedes Paiva, Fábio Friol; Okimoto, Fernando Sérgio [UNESP]; Bacarin, Giovani Boaventura [UNESP]; Dognani, Guilherme [UNESP]; Salmazo, Leandra Oliveira; dos Santos, Renivaldo José [UNESP]; Cabrera, Flávio Camargo [UNESP]; Job, Aldo Eloizo [UNESP] (SAGE Publications, 2023)
With the advances in the field of civil construction and the world population growth, the development of policies is necessary for the management and reuse of generated residue. Thus, the present work proposes the use of expanded natural rubber as a polymeric matrix incorporated with eucalyptus filler as a reinforcing filler for the production of composites. Thermal insulation capacity was determined by the transient plane source and acoustic method by impedance tube. NR/W40 foam showed enhanced the acoustic insulation capacity. The maximum absorption of NR/W40 was 0.83, at 3257 Hz, which is three times higher than natural rubber foam. Highly inhomogeneous cell structures were observed with large, interconnected pores, improving the acoustic performance. Sound absorption coefficient for natural rubber foam with 40% wood (0.83 ± 0.046) was similar to PU foam (0.97 ± 0.009) with 20 mm in thickness, a density of 47 kg/m3 and 98% open cell content it is a well-known acoustic absorbent in the building sector. The NR/W40 sample recorded the best acoustic performance among the NR foams analyzed in this work, maintaining good sound absorption above 1500 Hz, demonstrating a possibility of wood reuse as a filler in based-rubber foam for acustic insulation.
Keywords: Composites; compression; elastomers; foams